Treatment of patients with knee cartilage injury combined with lesions of the anterior crucial ligament and meniscus - Strafun, Sergey; Kostogryz, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Purpose: to study the possibility to use rational arthroscopic tactics of treatment and duration of rehabilitation of patients with injured knee cartilage combined with the anterior cruciate ligament (ACL) and menisci lesions on the basis of retrospective analysis of 735 knee joint surgeries with using of arthroscopic methods. Methods: combined injury of the joint cartilage of different severity was diagnosed in 519 patients (71.7 %), primary ACL lesion was observed in 221 patients. Meniscectomy was performed in 514 patients. In 106 patients with menisci and ACL lesions posttraumatic changes in joint cartilage of different severity according to Outerbridge were detected. In accordance with this patients were categorised into 4 groups. The 5th group (control) contains patients with ACL and meniscus lesions without any changes in joint cartilage. Patients with menisci lesions in 97% of cases underwent partial resection of the injured part, and just in 3% (cases of paracapsular injuries) meniscus suturing was performed. In 91% patients meniscus posterior horn lesions were revealed, in 6% - injuries of the meniscus body, and just in 3% of all meniscus lesions anterior horn of meniscus was injured. Results: for restoration of ACL injured were used tendons of semitendinous and gracilis muscles. In postoperative period we recommended offloading of the operated lower extremity depend on changes in joint cartilage but not longer than 6 months after surgery. Thus in case of changes in cartilage of the first grade no other manipulations on cartilage except restoration of intraarticular structures were performed. In cases of changes in cartilage of the second and third grades we performed vaporization of its injured parts, in cases of the fourth grade osteoperforation of the defected segments was done. Conclusions: it was confirmed that arthroscopy is the «gold standard» in diagnostics and treatment of injured structures of knee joint enabling visualisation of the degree and depth of joint cartilage changes, determining of indications for appropriate treatment, performing of medicinal manipulations, planning adequate comprehensive postoperative therapy and rehabilitation. Intraoperative tactics of treatment of patients with combined ACL, meniscus and joint cartilage lesion depends on severity of cartilage changes. Duration of postoperative rehabilitation increased with the growth of severity of joint cartilage changes. Therefore, combination of arthroscopic treatment of injured joint cartilage injury of ІІІ-ІV grades and proper rehabilitation in young patients now remains the most relevant and requires further study and improvement.